Hmyz - Insect nach einem Theaterstück von Karel Čapek und Josef Čapek - Švankmajer, Jan 1934-; Olha, Adam; Růžička, Jan 1959-; Lábus, Jiří 1950-; Budař, Jan 1977-; Lichý, Norbert (Athanor, 2019)
A group of actors meet in the Czech Republic's filthiest theatre to rehearse Karel and Josef Čapek's 1924 play "Pictures from an Insects Life" in Czech director Jan Švankmajer's squirm-inducing film "Hmyz", a ribald piece of surrealism that blends the political themes of the original play into both its fictional recreation and the actual behind-the-scenes filmmaking of the movie itself. The result is weird, wild, and for Švankmajer fans, a pure delight. This is probably the final film for the 83-year-old filmmaker, and was financed in part thanks to contributions from Kickstarter; the result is a unique experience that gives personal insight into both the filmmaker and his craft. [www.praguereporter.com]
Keywords: DVD-Video